A review on synthetic procedures and applications of phosphorus oxychloride (POCl3) in the last biennial period (2018–19). (20th October 2020) - Amin, Shaista; Alam, M. Mumtaz; Akhter, Mymoona; Najmi, A. K.; Siddiqui, Nadeem; Husain, Asif; Shaquiquzzaman, M.
Abstract: Phosphorus oxychloride, POCl3, an important phosphorus compound, has diverse applications in synthetic chemistry. It plays an important role in chlorination, Vilsmeier Haack reaction, dehydration and cyclization which have been highlighted here. Moreover, different reaction conditions implied and reported in the literature along with the general mechanism are provided briefly in this review. This review provides an insight into the recent applications of phosphorus oxychloride as a reagent in organic syntheses in the last two year i.e. 2018–19. Graphic abstract: